CrimeID: Towards Crime Prevention and Community Safety in Indonesia using Mobile and Web Technology - Purnomo W.P., Yohanes Sigit; Indriasari, Theresia Devi; Anindito, Kusworo; Andrean, Yoshua; Prasetyo, Jaka Galih (International Journal of Interactive Mobile Technologies (iJIM), 2019)
The rate of crime incidence in Indonesia is quite high. Some efforts to prevent crime and to create community safety have been already conducted. However, the information technology has not been implemented yet. CrimeID could be a technology tool for both individual and collective crime prevention. The citizen could participate individually as a crowd to annotate the crime data from news article through the crowdsourcing platform using gamification concept. The collected data could be used to raise the awareness among community members of the crime that happens surrounding them by using the location-aware system.